1982
DOI: 10.1111/j.1600-0897.1982.tb00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovum Factor: A First Signal of Pregnancy?

Abstract: Previous studies have shown that, in the mouse, a factor is produced by the fertilized ovum within 24 h of mating. It cooperates with prolactin to stimulate ovarian production of component B or early pregnancy factor (EPF). This paper presents an initial characterization of the substance, termed ovum factor (OF). An indirect assay based on the rosette inhibition test for EPF has shown that OF is first released upon penetration of the ovum by the fertilizing spermatozoon. OF continues to be produced at least un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 9 publications
2
41
0
Order By: Relevance
“…However, a specific stimulus is needed, e.g. spermatozoa, hyaluronoglucuronidase or Ca2+-and Mg2+-free medium, because ovum factor is not released from the cells either by diffusion or after sonic disruption (Cavanagh et al 1982) The results demonstrate the presence of EPF-A in serum. EPF-B was prepared by incubation of dioestrous mouse ovaries with ovum factor and prolactin as described by Cavanagh et al (1982).…”
Section: Production Of Epfmentioning
confidence: 54%
See 4 more Smart Citations
“…However, a specific stimulus is needed, e.g. spermatozoa, hyaluronoglucuronidase or Ca2+-and Mg2+-free medium, because ovum factor is not released from the cells either by diffusion or after sonic disruption (Cavanagh et al 1982) The results demonstrate the presence of EPF-A in serum. EPF-B was prepared by incubation of dioestrous mouse ovaries with ovum factor and prolactin as described by Cavanagh et al (1982).…”
Section: Production Of Epfmentioning
confidence: 54%
“…unpublished data), pig and sheep ova (H. Morton, unpublished data), as well as mouse ova (Cavanagh et al 1982), have all been found to produce ovum factor, which is not species-specific in its biological activity; ovum factor produced from cultured human or pig embryos acts in the mouse similarly to mouse ovum factor. Furthermore, Nancarrow et al (1981) have shown that, after an infusion of mouse ovum factor, EPF can be detected in the serum of oestrous sheep.…”
Section: Production Of Epfmentioning
confidence: 99%
See 3 more Smart Citations